THE NONMARKET ENVIRONMENT OF THE WINE INDUSTRY IN THE REPUBLIC OF MACEDONIA: THE CASE OF WINES OF MACEDONIA ASSOCIATION (FROM MARKET RIVALS TO ALLIES IN THE NONMARKET ENVIRONMENT) - Zarić, Sinisa; Ilievski, Igor (Economics of Agriculture, 2018)
The production of wines contributes strongly to the overall export of Macedonia, having a big tradition and potentials for further development due to good climate and soil conditions. In the same time, the production of wine, in many countries, is one of the highly regulated sectors. Thus, there is a need for wine manufacturers to deal actively with the nonmarket environment and influence on regulatory legislation. Having in mind a big importance of the EU market for the export of Macedonian wines, there is a need for further harmonization with the EU regulation. Subject of this paper is a critical analysis of the economic policies in the feld of agricultural production focused on the policy of subsidies. The aim is to show importance of having the active role of the wine producers in the nonmarket environment. Qualitative methodology is based on the experiences of the Wines of Macedonia (WOM) Association and, indicating the possibility of transforming the market rivals into nonmarket allies.